APLIKASI VIRTUAL REALITY GALERY SEJARAH KABUPATEN PINRANG MENGGUNAKAN VR BOX 3D - Megah Sari, Dian; Majid, Firdaus (Fakultas Teknik Universitas Muhammadiyah Parepare, 2021)
Nowadays, people's enthusiasm in studying history, especially the history of their respective regions, is currently decreasing, so that knowledge about the history of the region is minimal and coupled with the lack of literature on the history of an area and the lack of initiative and creativity of local governments in educating history to the public. Responding to problems like this, new breakthroughs are needed such as field trip methods combined with a technological device, such as one of the visual technologies that can be used for field trips is virtual reality technology. By applying the throw away prototype method as a method in making applications where the throw away prototype method is a method that leads to presentation results only, aims to visualize a system that is being built based on user comments, the next prototype continues to be built until it can visualize a real working system. Tests carried out using the black box method and white box testing on the Pinrang Regency historical gallery application. The results of this study can be used by the people of Pinrang Regency, especially for students as a means of learning history about Pinrang Regency.